A prospective observational study of demographic profile in patients of amoebic and pyogenic liver abscesses in a tertiary care hospital - Walwekar, Arun; Mirje, Mrutyunjay; Balaraddiyavar, Namrata; Walwekar, Rekha (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Liver abscesses, both amoebic and pyogenic, continue to be an important cause of morbidity and mortality in tropical countries. Pyogenic liver abscess is a serious, life-threatening condition with a high mortality rate that represents a diagnostic and therapeutic challenge. In India, due to poor sanitary condition and a lower socioeconomic status, amoebiasis is endemic and amoebic liver abscess accounts for 3-9% of all cases of amoebiasis. Aim and objectives of current study was to study demographic profile in patients of amoebic and pyogenic liver abscesses. Methods: A detailed history was taken from each of these patients and all of them were subjected to a through clinical examination. Results: The highest incidence occurred in the age group 31-50 years; males were more commonly affected than females. Fever and pain abdomen were the most consistently occurring symptoms. All the patients with liver abscess had abdominal tenderness. 17 patients (74%) with liver abscess were alcoholics. 8 patients (80%) with amoebic liver abscess were alcoholic as compared to 9 patients (69%) in pyogenic liver abscess. Conclusions: Pyogenic organisms were most common cause of liver abscess.